Influence of Impurities from Manufacturing Process on the Toxicity Profile of Boron Nitride Nanotubes. Issue 52 (14th November 2022) - Kodali, Vamsi; Kim, Keun Su; Roberts, Jenny R.; Bowers, Lauren; Wolfarth, Michael G.; Hubczak, John; Xin, Xing; Eye, Tracy; Friend, Sherri; Stefaniak, Aleksandr B.; Leonard, Stephen S.; Jakubinek, Michael; et al.
Abstract: The toxicity of boron nitride nanotubes (BNNTs) has been the subject of conflicting reports, likely due to differences in the residuals and impurities that can make up to 30–60% of the material produced based on the manufacturing processes and purification employed. Four BNNTs manufactured by induction thermal plasma process with a gradient of BNNT purity levels achieved through sequential gas purification, water and solvent washing, allowed assessing the influence of these residuals/impurities on the toxicity profile of BNNTs. Extensive characterization including infrared and X‐ray spectroscopy, thermogravimetric analysis, size, charge, surface area, and density captured the alteration in physicochemical properties as the material went through sequential purification. The material from each step is screened using acellular and in vitro assays for evaluating general toxicity, mechanisms of toxicity, and macrophage function. As the material increased in purity, there are more high‐aspect‐ratio particulates and a corresponding distinct increase in cytotoxicity, nuclear factor‐κB transcription, and inflammasome activation. There is no alteration in macrophage function after BNNT exposure with all purity grades. The cytotoxicity and mechanism of screening clustered with the purity grade of BNNTs, illustrating that greater purity of BNNT corresponds to greater toxicity. Abstract : Boron nitride nanotubes (BNNTs) are produced by hydrogen‐assisted BNNT synthesis and sequentially purified by various purification processes. Material characterization, acellular reactivity, cytotoxicity, inflammation, function, and mechanism of toxicity screening found BNNT is not overtly toxic, and the toxicity is primarily driven by increasing purity.